2005
DOI: 10.1590/s0100-29452005000100043
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da área foliar de plantas de lima ácida 'Tahiti' usando métodos não-destrutivos

Abstract: O objetivo desse estudo foi avaliar métodos não-destrutivos para a determinação da área foliar de plantas jovens de lima ácida 'Tahiti'(Citrus latifolia Tan.), em campo. Foram utilizadas informações de variáveis biométricas de 28 plantas jovens (0,07 a 1,44 m²) e imagens digitais da área frontal de cada planta (silhueta de copa). Essas variáveis foram correlacionadas com medidas diretas (contagem total de folhas x área foliar média). Como resultado, foi possível estimar a área foliar total das plantas (AFT) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In each defoliation, it was collected and counted all the leaves randomly taken from the canopy (Nl), measuring the maximum length (L) and maximum width (W) of 100 leaves. Mean values L and W were adopted to calculate the total leaf area of the tree (Equation 1) using a correction factor 'f ' equal to 0.7 (Coelho et al, 2005), allowing estimation of the initial value LA (without manual defoliation) and the determination of other post-defoliation values.…”
Section: Methodsmentioning
confidence: 99%
“…In each defoliation, it was collected and counted all the leaves randomly taken from the canopy (Nl), measuring the maximum length (L) and maximum width (W) of 100 leaves. Mean values L and W were adopted to calculate the total leaf area of the tree (Equation 1) using a correction factor 'f ' equal to 0.7 (Coelho et al, 2005), allowing estimation of the initial value LA (without manual defoliation) and the determination of other post-defoliation values.…”
Section: Methodsmentioning
confidence: 99%
“…Some methods and examples of how they are applied are cited in the literature, including the leaf disk method (Lopes et al, 2007), automatic planimeter (Mielke et al, 1995), leaf weight (Monteiro et al, 2005) and the gravimetric method (Norman and Campbell, 1989). Nondestructive methods include those that estimate leaf dimensions (Partelli et al, 2006), leaf areas using regression models (Moreira-Filho et al, 2007;Coelho-Filho et al, 2005) and those that use digital images and software for analysis. Methods involving the use of digital images can be destructive (if the leaves are removed from the plant) or non-destructive (if digital images of the leaves are captured without removal from the plant).…”
Section: Introductionmentioning
confidence: 99%
“…Close-range data collection became a subject of study with the popularization of portable sensors, as successfully shown in Koenig et al (2015) or Vázquez-Arellano et al (2016). Some studies focused on the use portable sensors in fruit growth monitoring using either active (Berk et al, 2016;Colaço et al, 2017;Escolà et al, 2017) or passive remote sensing sensors (Coelho Filho et al, 2005;Zhou et al, 2012;Linker, 2017). Given their high cost, these systems are usually not affordable for small holder farms and production estimates in several orchards are still based on visual counting techniques.…”
Section: Introductionmentioning
confidence: 99%